Meningkatkan Literasi Siswa Dengan Menggunakan Buku Cerita Bergambar Di SDN 3 Lakatan - Ririn Chintia Nuzulul (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2024)
This research was motivated by the discovery of problems related to initial reading literacy skills in class II of Lakatan 3 State Elementary School, which still shows that there are still some students who experience difficulties in reading literacy, especially initial reading. The aim of this research is to increase students' initial reading literacy by using picture story books using classroom action research methods in collaboration with the homeroom teacher for class II at State Elementary School 3 Lakatan. This research uses Kurt Lewin's research model which has 4 stages in one cycle. The results of the research show that learning using picture storybook media can increase students' interest and motivation in learning so that the quality of the learning process increases. Using story books with pictures can also increase the literacy of students in class II of Lakatan 3 State Elementary School. The results of the research scores showed an increase from cycle I to cycle 2. The average percentage score increased from 65.4% to 86.1%. Classical completion in cycle I to cycle II also increased from 38.5% to 84.6%.